Synthesis and Phase Transition Behaviours of New Chalcone Derivatives - S. T. Ha; Y. W. Low (Journal of Chemistry)
A series of new chalcone derivatives with a general formula of C11H27COOC6H4COCH=CHC6H4X where X=F, Cl, Br, and NO2 were well synthesized and crystallized from organic solution. The physical properties as well as the chemical formulations of these compounds were determined by spectroscopic techniques (FTIR, and 1H and 13C NMR). Differential scanning calorimetry (DSC) and polarizing optical microscopy (POM) techniques were employed to study their transition temperatures and mesophase characteristics. DSC thermograms of compounds with fluoro and nitro substituents displayed direct isotropization and recrystallization during heating and cooling processes. Chloro and bromo analogues exhibited Cr1-to-Cr2 transition within the crystal phase region. It was also found that enone linkage showed fewer tendencies to exhibit mesomorphic property compared to imine linkage. However, when enone linkage is combined with other central linkages and additional phenyl rings, it turns conducive to mesomorphism.